Penaksiran Cadangan Batu Gamping Menggunakan Metode Cross Section di Kalirejo, Kulonprogo, Daerah Istimewa Yogyakarta - Andrawina Andrawina; Venty Lestari (Jurnal Kendali Teknik dan Sains, 2026)
Reserve estimation is a critical stage in mine planning that determines the economic feasibility of a mining project. This study aims to estimate the volume and tonnage of limestone reserves in Kalirejo Village, Kulon Progo District, Special Region of Yogyakarta, using the cross section method within a 5 hectare concession area. Primary data were collected through theodolite and GPS measurements, resulting in 29 coordinate points. Three cross sections, namely the red, blue, and pink cross sections, were created based on topographic data processed using ArcGIS. The area of each cross section was calculated using the graphical square method at a scale of 1:2000, where one grid square represents 100 m². The calculated areas were 33,940 m² for the red cross section, 36,645 m² for the blue cross section, and 31,947 m² for the pink cross section. The total reserve volume was calculated using the prismoidal formula, yielding 6,862,853 m³, with an error rate of 0.28% compared to the ArcScene calculation. With a limestone density of 2.5 tons/m³, the total reserve tonnage that can be produced over a 10-year mine life is 17,157,132.625 tons. The stripping ratio value of 0.00305 indicates highly favorable conditions for open-pit mining operations. The production target is set at 1,039,596.65 tons/year, equivalent to 193 tons/hour. This study validates the accuracy of the manual cross-section method combined with GIS software for limestone reserve estimation at the exploration scale.